PELAKSANAAN PERNIKAHAN ETNIS MELAYU DI DESA KEBUN LADO KECAMATAN SINGINGI - Rahmadania, Lisa; Isjoni, Isjoni; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Indonesia is a unitary state which includes islands and various communities. The community that lives is a society that has been handed down to occupy a certain area and is based on the traditional management power of ethnic groups. The existence of various cultures and communities that live allows social interaction between them. One of the interactions that occur in society is marriage. The objective of this study was to (1) To find out the history of the arrival of the community in Lado Village, Singingi District (2) To find out the background of Malay holding a wedding and wedding custom procedures in Lado Village Singingi District (3) To find out what Minangkbau people think about the usage of Minangkabau wedding customs by Malay (4) To find out the values contained in the implementation of wedding customs in Lado Village, Singingi District. The research method used in this research is a descriptive research method using a qualitative approach and using data collection techniques such as observation, interviews, and documentation. The history of the arrival of the community in Lado Village, Singingi District. The background distinguishes marriage customs as well as customary marriage procedures which consist of events such as Mamak uma and soko pisoko at the men's house, Mamak uma and sokopisoko at the women's house, Maanten tando or engagement events, Bainai night, Bainai Night, Akad nikah, Tepuk Tepung Tawar, pick Marapulai and greet at the Daro Children's Home (Ulu Jawek Taimbang Taimo) Towards Mintua and the wedding party Minangkbau ethnic opinion with the implementation of Minangkabau wedding customs by ethnic Malays and the values contained in the implementation of wedding customs in Lado village.Key Words: History, Customs, Wedding, Cultural Value